A study on employability skills among graduate / Nur Sabiha Zulaikha Mohd Hata and Nurul Aqilah Mohd Jefri - Mohd Hata, Nur Sabiha Zulaikha; Mohd Jefri, Nurul Aqilah (Faculty of Business and Management, 2014)
An employability skill is a passport for an individual to step into a challenging working industry. The more employability skills that they possess the greater the possibility and chance for them to get better placement. Employability skills play important roles in defining graduates efficiency and performance. Lack of employability skills will lead to low productivity and will lead to unemployment. The past researcher shows that there are many employability skills that can add the value of graduates. Present research study on four employability skills which is problem solving and adaptability skills, human skills, English language proficiency and literacy skills and also communication skills. This study is conducted to determine the level of employability skills among graduate university in Johor Bahru and involved 120 respondents in different courses. Result of the present study show that Human Skills is the highest level of employability skills. Recommendation for future research has also having been discussed.